Visible-Light-Driven Photocatalytic Degradation of Rhodamine B over Bimetallic Cu/Ti-MOFs - Thuy Bich Tran; Thanh Trung Nguyen; Sy Trung Do; Hong Tham Thi Nguyen; Kim Ngan Thi Tran; Kim Oanh Thi Nguyen (Universitas Gadjah Mada, 2022)
The first copper-doped titanium-based amine-dicarboxylate metal-organic framework was synthesized by the solvothermal approach in this article, with a Cu2+/Ti4+ ratio of 0.15 (15% Cu/Ti-MOFs). X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectra, N2 adsorption-desorption studies, and UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS) were all used to identify the crystalline and properties of the semiconductors. The rate constants of 15% Cu/Ti-MOFs to degrade Rhodamine B (RhB) were roughly two times higher than NH2-Ti-MOFs. Furthermore, 15% Cu/Ti-MOFs photocatalysts remained stable after three cycles. The trapping test revealed that the principal active species in the degradation performance were hydroxyl radicals and holes.